THE ROLE OF (ECONOMIC) INSTITUTIONS IN ATTRACTING FOREIGN DIRECT INVESTMENT IN BOSNIA AND HERZEGOVINA - Amra Babajić; Mirnesa Baraković-Nurikić (Economic Review)
In the context of encouraging economic growth and development, every country needs adequate financial resources, including Bosnia and Herzegovina (hereinafter BiH). One of the key mechanisms in the context of obtaining financial resources refers to foreign direct investment (hereinafter referred to as FDI). FDI can be a very important channel for technology transfer between countries or simply a way to promote international trade through greater access to foreign markets, while from the aspect of international economic integration it can create stable and long-term connections between countries. Attracting foreign investors requires an adequate investment environment in the country, so institutions are of crucial importance for creating a suitable environment for FDI. Attracting FDI requires an economically stable country with clearly defined directions of development. Considering the large number of studies that claim institutions are of crucial importance for economic development, the goal of this paper is to determine whether institutions in BiH contribute to its economic development, through one of the key mechanisms for accelerating economic development – FDI. The period of 20 years, i.e., 2002-2022, was analyzed. Correlation analysis confirmed a positive relationship between FDI and Voice and Accountability and a negative relationship between FDI and Rule of Law, while linear regression indicates that only Rule of Law has a statistically significant and positive impact on FDI in BiH. The findings of this research can serve the holders of economic power in BiH in designing strategies and policies for economic growth and development, i.e., strengthening economic institutions and attracting FDI.